PENDIDIKAN KESEHATAN SEKOLAH SEBAGAI PROSES PERUBAHAN PERILAKU SISWA - Indah Prasetyawati Tri Purnama Sari (Jurnal Pendidikan Jasmani Indonesia, 2013)
Health education is a process of change in a person with a view to achieving a healthy degree. The purpose ofhealth education is to change behavior that is not healthy to be healthy both at the individual, group, and community.Learning process involves the interaction of teachers as educators and students as learners. Students as subjectsin the study of health education are expected to implement healthy lifestyle in everyday life. Teachers as educatorsshould be able to realize the change in the behavior of students who have a responsibility for the health of the studentsthemselves. Responsibility for health can be seen through the behavior of students in the habit (behaviorsm) ineveryday life. Healthy behavior change through health education is not simply transfer the knowledge and attitudesof teachers, but how students can behave in achieving a balance between the environment, behavior, and human.Health education in schools can be realized through the School Health Unit (UKS).Keywords: Health Education, Behavior, Students